2013
DOI: 10.1080/10410236.2013.804486
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Disease Practices Among a Lower SES, Multicultural, Nonurban, U.S. Community: The Roles of Vaccination Efficacy and Personal Constraints

Abstract: In spite of knowledge that early vaccination against contagious diseases such as swine flu reduces morbidity and contains contagion, rates of vaccination in the most recent three annual disease cycles were lower than anticipated. Some previous research suggests that lower socioeconomic status, mixed-racial population composition, and a nonurban environment may all contribute to lower vaccination rates. This study adopts the health belief model to create two composite indexes-vaccine efficacy and personal const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Mo & Lau 7 found that government recommendations were positive for vaccination, in the form of recommendations in the mass media and advertisements. Meanwhile, Avery & Lriscy 26 found that stimulus for vaccination was associated with communication via social networks. Corace et al 27 found higher vaccination rates among individuals whose family members and friends thought that vaccination was important, demonstrating that other people can positively influence vaccination behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Mo & Lau 7 found that government recommendations were positive for vaccination, in the form of recommendations in the mass media and advertisements. Meanwhile, Avery & Lriscy 26 found that stimulus for vaccination was associated with communication via social networks. Corace et al 27 found higher vaccination rates among individuals whose family members and friends thought that vaccination was important, demonstrating that other people can positively influence vaccination behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Social media sites like Twitter show promise for public health efforts (Avery & Lariscy, 2014; Broniatowski et al, 2013). “Social listening” (Cole-Lewis et al, 2015) allows for an examination of vaccination-related beliefs and can serve as an early indicator of shifts in public opinion that might not be captured in traditional surveys due to high costs (Dredze et al, 2016), and sampling (Call et al, 2011; Duggan et al, 2015) and social desirability biases (Krumpal, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Twitter is a platform for health-related information (Scanfield et al, 2010) and exposure to vaccine-related information on social media has been associated with vaccine-related behavior (Avery & Lariscy, 2014). Further, geo-tagged Twitter data allow researchers to identify geographical regions where anti-vaccination beliefs are predominant.…”
Section: Introductionmentioning
confidence: 99%
“…This pilot study was performed in a single geographic area, with minimal heterogeneity of the study population which limits the generalizability of the results. Also, there are known to be culturally-specific vaccination attitudes and beliefs [ 43 46 ] which would not likely be addressed by TeenVaxScene as it was designed for the general public. Finally, our website was available only in English and only on an iPad, and was therefore not likely useful for non-English speakers and those who were not familiar with how to use an iPad.…”
Section: Discussionmentioning
confidence: 99%